2016
DOI: 10.1002/anie.201510504
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structural Characterization of Magnesium‐Substituted Polystibides [(LMg)4Sb8]

Abstract: Redox reactions of [(L(1,2) Mg)2 ] and Sb2 R4 (R=Me, Et) yielded the first Mg-substituted realgar-type Sb8 polystibides [(L(1,2) Mg)4 (μ4 ,η(2:2:2:2) -Sb8)] (L(1) =HC[C(Me)N(2,4,6-Me3 C6 H2)]2, L(2) =HC[C(Me)N(2,6-i-Pr2 C6 H3)]2). Compounds [(L(1,2) Mg)2] serve both as reducing agents, initiating the cleavage of the Sb-C bonds, and as stabilizers for the resulting Sb8 polyanion. The polystibides were characterized by NMR and IR spectroscopies, elemental analysis, and X-ray structure analysis. In addition, resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 89 publications
4
36
0
1
Order By: Relevance
“…All calculated bond lengths within the Ga 2 Sb 2 ( 1 , 2 ) and Ga 2 Sb 4 ( 3 ) cores (BP86‐D3/def2‐SVP level of theory, Tables S2–S4 in the Supporting Information) agree well with the corresponding experimental values (Δ r =0.02–0.08 Å). As predicted by atoms in molecules (AIM), electron localization function (ELF), and natural bond orbital (NBO) analyses, all Sb−Sb bonds in 1 , 2 , and 3 are covalent in nature (Tables S2–S4, Figures –), in accordance with recently reported computational data for these types of complexes …”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…All calculated bond lengths within the Ga 2 Sb 2 ( 1 , 2 ) and Ga 2 Sb 4 ( 3 ) cores (BP86‐D3/def2‐SVP level of theory, Tables S2–S4 in the Supporting Information) agree well with the corresponding experimental values (Δ r =0.02–0.08 Å). As predicted by atoms in molecules (AIM), electron localization function (ELF), and natural bond orbital (NBO) analyses, all Sb−Sb bonds in 1 , 2 , and 3 are covalent in nature (Tables S2–S4, Figures –), in accordance with recently reported computational data for these types of complexes …”
Section: Resultssupporting
confidence: 87%
“…Upon heating, 4 was converted into [(LGaNMe 2 ) 2 (μ,η 1:1 ‐Sb 4 )] 5 , the first Sb analogue of bicyclo[1.1.0]butane, which formally contains a [Sb 4 ] 2− dianion . In addition, reduction reactions of distibines R 4 Sb 2 (R=Me, Et) with LM (M=Al, Ga) proceeded with insertion of LM into the weak Sb−Sb bond and subsequent formation of LM(SbEt 2 ) 2 , whereas analogous reactions with stronger reducing Mg I reagents formed the Zintl‐type [Sb 8 ] 4− anions [(LMg) 4 (μ 4 ,η 2:2:2:2 ‐Sb 8 )] and [(L′Mg) 4 (μ 4 ,η 2:2:2:2 ‐Sb 8 )] {L′=HC[C(Me)N(2,4,6‐Me 3 C 6 H 2 )] 2 } . Very recently, we showed that reduction reactions of cyclo‐tetrastibine [Cp*Sb] 4 , in which the central Sb atoms adopt the formal oxidation state +I, with LGa and [L′′Mg] 2 (L′′= i Pr 2 NC[N(2,6‐ i Pr 2 C 6 H 3 )] 2 ), yielded [(LGa) 2 (μ,η 2:2 ‐Sb 4 )] and [(L′′Mg) 4 (μ 4 ,η 1:2:2:2 ‐Sb 4 )] .…”
Section: Introductionmentioning
confidence: 99%
“…Comparable findings were reported for reactions of LAl with diphosphines, whereas the reaction of LGa with [Cp*Sb] 4 (Cp*= C 5 Me 5 ), in which the Sb atoms adopt the formal oxidation state +I, yielded [(LGa) 2 (μ,η 2:2 ‐Sb 4 )] . Interestingly, analogous reactions with the stronger reducing Mg I reagents occurred with formation of [(LMg) 4 (μ 4 ,η 2:2:2:2 ‐Sb 8 )] and [(L′Mg) 4 (μ 4 ,η 2:2:2:2 ‐Sb 8 )] (L′=HC[C(Me)N(2,4,6‐Me 3 C 6 H 2 )] 2 ), containing the Zintl‐type [Sb 8 ] 4− anion, as well as [(L′′Mg) 4 (μ 4 ,η 1:2:2:2 ‐Sb 4 )] (L′′= i Pr 2 NC[N(2,6‐ i Pr 2 C 6 H 3 )] 2 ) containing a [Sb 4 ] 4− tetraanion, respectively …”
Section: Introductionmentioning
confidence: 57%
“…For instance, the Ga2−Sb1 bonds are significantly shorter than the Ga−Sb σ ‐bonds found in Lewis acid base adducts, [R 2 GaSbR′ 2 ] 3 heterocycles (2.663(2)–2.722(3) Å) and monomeric [(dmap)Et 2 GaSb(SiMe 3 ) 2 ] (2.648(1) Å; dmap=4‐dimethylaminopyridine) with threefold‐coordinated Sb atom . They are also shorter in comparison to Ga−Sb bonds observed in (LGa) 2 Sb 4 (2.6637(11)–2.6779(11) Å), [L(X)GaSb] 2 (X=NMe 2 2.6200(4) Å; NMeEt 2.6169(5) Å; Cl 2.58178(19) Å), [{L(X)Ga} 2 ( μ , η 1:1 ‐Sb 4 )] (X=NMe 2 2.5975(5) Å; Cl 2.6008(13) Å), and base‐stabilized [Cl( n ‐Pr 2 PhP)GaSbSi‐ i Pr 3 ] 2 (2.635(1)–2.655(1) Å) . The Ga−X bonds steadily increase in length (1.7923(9) Å 1 ; 2.2409(5) Å 2 ; 2.3917(3) Å 3 ; 2.6093(7) Å 4 ) due to the increasing atomic radii, as expected.…”
Section: Resultsmentioning
confidence: 99%
“…The Sb−Sb bonds (2.8205(3)–2.8437(3) Å) in cyclotristibine 6 (Figure ) are significantly elongated compared to Sb=Sb double bonds reported for the Ga‐coordinated distibenes [L(X)GaSb] 2 as mentioned before, but agree very well with the Sb−Sb single bond values reported for distibines R 4 Sb 2 , which were found to range from 2.797(3) to 3.030(3) Å, and cyclostibines [RSb] x ( x= 3–6; 2.794(4)–2.883(4) Å) . In addition, the only structurally characterized cyclotristibine [(Me 3 Si) 2 CHSb] 3 showed almost identical Sb−Sb bond lengths (2.8188(6)–2.8453(6) Å) .…”
Section: Resultsmentioning
confidence: 99%